Of Cripples and Bags. Risk and the Stuff of Reality - D’Andrea, Fabio (Italian Sociological Review, 2017)
A better understanding of what knowledge is and how it works is a crucial tool to cope with the current paradigm shift and the uncertainty it is causing everywhere. It can shed some light on the imaginal foundations of human enterprise, even of reality itself. Reality is in fact the result of innumerable definitions and agreements, to which modernity gave an objective look and claim. Science, however, has grown past this comforting stage and revealed it as wishful thinking. As modern institutions were planned and realized in the light of such convictions, they are no longer up to dealing with a world where certainty is not to be found. Beck’s analysis of global risks clearly shows the ‘organized irresponsibility’ that stems from this state of things. Taking Beck’s insight as a new starting point, it is possible to focus on reality’s complex texture – where real, possible and imagined seem to blend in a dynamic mix – and to advocate the urgency of new heuristic perspectives and frames where imagination and its structures are given back their dignity as fundamental keys to the understanding of human action and decision-making.